Range of Motion of the Upper Extremity in a Healthy Pediatric Population: Introduction to Normative Data - Da Paz, Stephanie Nunes; Stalder, Andreas; Berger, Steffen; Ziebarth, Kai (European Journal of Pediatric Surgery, 2016)
Objective In the pediatric population traumatic injuries of the upper extremity are common. After therapy a decision has to be made if the mobility of the joint lies within a normal range. The purpose of this study was to give an introduction to normative data. We investigate if there is a significant difference in the range of motion (ROM) between male and female probands and furthermore, if an effect of the age can be detected.Methods We performed an institutional review board-approved study of healthy girls and boys aged between 2 and 16 years without any medical history of an upper extremity fracture. We investigated the active ROM of the elbow, wrist, metacarpophalangeal, and interphalangeal joints. Furthermore, age, handedness, weight, and height were recorded. A total of 171 adolescents with a mean age of 10.6 years were included and separated into four cohorts by age: 2 to 5, 6 to 10, 11 to 13, and 14 to 16 years.Results We found significant differences between the genders in the age group from 11 to 13 years for the flexion of the elbow, the pronation, the flexion of the interphalangeal joint of the thumb, as well as the flexion of the metacarpophalangeal joints of digitus II to V. Furthermore, a significant difference in the same joints except from the elbow flexion could be demonstrated between the genders.Conclusion Our study contributes normative data for upper extremity ROM in the pediatric population and presents a gender-related difference in certain joints.Clinical Relevance Normative data for the ROM of upper extremity joints in children is helpful for the evaluation of pediatric orthopedic patients and provides the framework for therapeutic resolution. Since a great number of traumatic injuries in children affect the upper extremity, this information may help the physician to estimate the impact of the injury and decide on the therapeutic management.
Keywords: upper extremity; pediatric population; range of motion